GEOCHEMICAL DISTRIBUTION OF ELEMENTS IN WATERS AND SEDIMENTS OF PLESENSKA RIVER WITH A SPECIAL FOCUS ON THE PRESENCE OF HEAVY METALS (Natural Resources and Technology, 2025)
This paper presents the data from laboratory examinations of water and sediments in the autumn and early spring (September 2024 and February 2025). The examinations included waters and sediments from Plesenska River and the confluence of Kiselica River with Zletovska River, as well as a spring located in the immediate vicinity of Plesenska River. The water examinations were conducted to assess the actual condition and geochemical distribution of elements during the two studied periods, with a special focus on the presence of heavy metals. To obtain additional information about the components transported by the water flow and to gain insight into the cause-and-effect relationships and mechanisms, sediment examinations were also performed. The results obtained from the laboratory tests of water and sediments were analyzed in details, and correlation diagrams were made with interpretations of the findings.
Keywords: water, sediments, distribution, pH, heavy metals